Beban Kerja, Stres Kerja, dan Motivasi Kerja terhadap Kinerja Perawat bagian Keperawatan pada Rumah Sakit Umum Daerah Arifin Ahmad Pekanbaru - Syarfan, La Ode; Indra Safri (Journal Of Administration and Educational Management (ALIGNMENT), 2025)
This study aims to analyze the effect of workload, work stress, and work motivation on nurse performance at Arifin Ahmad Regional General Hospital, Pekanbaru. The research method used is a quantitative method with a descriptive and associative approach. Data collection was carried out through a Likert-scale closed questionnaire, in-depth interviews, and direct observation, and supported by secondary data from hospital documentation. Validity and reliability tests showed that all research instruments were valid and reliable. Data analysis used multiple linear regression that met the classical assumptions. The results showed that the three independent variables, namely workload, work stress, and work motivation, partially and simultaneously had a significant effect on nurse performance. The coefficient of determination (R²) of 0.837 indicated that 83.7% of the variation in nurse performance could be explained by the three variables, while the rest was influenced by other factors outside the study. The conclusion is that increasing workload, work stress, and work motivation significantly affect the improvement of nurse performance.   Keywords: Workload, Performance, Work Motivation, Work Stress